So just what is going on here in some way we can

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ) (a) [Solution] [Solution] [Solution] [Solution] [Solution] Solution (a) ( f o h ) ( x ) Not much to do here other than run through the formula. © 2007 Paul Dawkins 193 http://tutorial.math.lamar.edu/terms.aspx College Algebra ( f o h) ( x) = f éh ( x )ù ë û = f é x + 1ù ë û = ( ) 2 x +1 - 3 = x +1- 3 = x-2 [Return to Problems] (b) ( h o f ) ( x) Again, not much to do here. ( h o f ) ( x ) = h é f ( x )ù ë û = h é x 2 - 3ù ë û = x2 - 3 + 1 = x2 - 2 [Return to Problems] (c) ( f o f ) ( x) Now in this case do not get excited about the fact that the two functions here are the same. Composition works the same way. ( f o f ) ( x) = f é f ( x )ù ë û 2 = f é x - 3ù ë û = ( x 2 - 3) - 3 2 = x4 - 6 x2 + 9 - 3 = x4 - 6 x2 + 6 [Return to Problems] (d) ( h o h ) ( 8 ) In this case, unlike all the previous examples, we’ve got a number in the parenthesis instead of an x, but it works in exactly the same manner. ( h o h ) ( 8 ) = h é h ( 8) ù ë û = h é 8 + 1ù ë û = hé 9ù ë...
View Full Document

This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.

Ask a homework question - tutors are online